The wage premium of globalization: Evidence from European mergers and acquisitions - Harald Oberhofer; Matthias Stöckl; Hannes Winner (Kiel Institute for the World Economy (IfW), 2012)
We provide evidence on the impact of globalization on labor market outcomes analyzing pay differences between foreign-acquired and domestically-owned firms. For this purpose, we use firm level data from 16 European countries over the time period 1999-2006. Applying propensity score matching techniques we estimate positive wage premia of cross-boarder merger and acquisitions (M&As), suggesting that foreign acquired firms exhibit higher short-run (post-acquisition) wages than their domestic counterparts. The observed wage disparities are most pronounced for low paying firms (with average wages below the median). Finally, we find systematic wage premia in Western European countries, but not so in Eastern Europe.
Keywords: C21; F15; G34; J31; 330; Globalization; mergers and acquisitions; wage effects; propensity score matching